Detection of amyloid beta peptides in body fluids for the diagnosis of alzheimer's disease: Where do we stand?. (17th February 2020) - Veerabhadrappa, Bhavana; Delaby, Constance; Hirtz, Christophe; Vialaret, Jérôme; Alcolea, Daniel; Lleó, Alberto; Fortea, Juan; Santosh, Mysore Sridhar; Choubey, Shushil; Lehmann, Sylvain
Abstract: Alzheimer's disease (AD) is an incurable neurodegenerative disease characterized by progressive decline of cognitive abilities. Amyloid beta peptides (Aβ), Tau proteins and the phosphorylated form of the Tau protein, p-Tau, are the core pathological biomarkers of the disease, and their detection for the diagnosis of patients is progressively being implemented. However, to date, their quantification is mostly performed on cerebrospinal fluid (CSF), the collection of which requires an invasive lumbar puncture. Early diagnosis has been shown to be important for disease-modifying treatment, which is currently in development, to limit the progression of the disease. Nevertheless, the diagnosis is often delayed to the point where the disease has already progressed, and the tools currently available do not allow for a systematic follow-up of patients. Thus, the search for a molecular signature of AD in a body fluid such as blood or saliva that can be collected in a minimally invasive way offers hope. A number of methods have been developed for the quantification of core biomarkers, especially in easily accessible fluids such as the blood, that improve their accuracy, specificity and sensitivity. This review summarizes and compares these approaches, focusing in particular on their use for Aβ detection, the earliest biomarker to be modified in the course of AD. The review also discusses biomarker quantification in CSF, blood and saliva and their clinical applications.